2015
DOI: 10.1103/physrevb.91.165311
|View full text |Cite
|
Sign up to set email alerts
|

Heating-frequency-dependent thermal conductivity: An analytical solution from diffusive to ballistic regime and its relevance to phonon scattering measurements

Abstract: The heating frequency dependence of the apparent thermal conductivity in a semi-infinite body with periodic planar surface heating is explained by an analytical solution to the Boltzmann transport equation. This solution is obtained using a two-flux model and gray mean free time approximation, and verified numerically with a lattice Boltzmann method and numerical results from the literature. Extending the gray solution to the non-gray regime leads to an integral transform and accumulation-function representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 52 publications
3
57
0
Order By: Relevance
“…iωt , where ω is the angular frequency [15,20]. Case II: there is an oscillating heat current at the surface I Q (t) = I 0 Q e iωt [5].…”
Section: A Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…iωt , where ω is the angular frequency [15,20]. Case II: there is an oscillating heat current at the surface I Q (t) = I 0 Q e iωt [5].…”
Section: A Boundary Conditionsmentioning
confidence: 99%
“…These differences originate in how the angle-dependence of phonon transport is approximated; we replace the x-projected phonon velocity distribution with its angle-averaged value, v + x , while in Refs. [15,20] solutions come from taking the two lowest order moments of the BTE. Note that an isotropic medium assumption is not required, and that the input parameters v + x and λ can be extracted for any phonon dispersion and scattering time (see Eqns.…”
Section: A Analytical Solutionsmentioning
confidence: 99%
“…Vermeersch et al reported a truncated Lévy formalism to analyze the quasiballistic motion of thermal energy in semiconductor alloys [15,16]. Two-channel models, in which low-and highfrequency phonons are described by the Boltzmann transport equation (BTE) and heat equation, have been applied to analyze the quasiballistic thermal transport in transient grating [17] and thermoreflectance experiments [18,19]. A McKelveyShockley flux method was adapted to describe phonon transport [20].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, it is also studied in the context of semiconductor alloys and it is found that the magnitude of the phononic thermal conductivity reduces as the frequency increases 11 . Theoretically, the electronic and the phononic dynamical thermal conductivity is discussed in the recent past by Shastry 12 and others [13][14][15][16] in different contexts such as in open systems, strongly correlated systems, semiconductor crystals, etc. In the present work, we explicitly derive the various expressions for the electronic thermal conductivity in case of metal with electron-impurity and electron-phonon interaction.…”
Section: Introductionmentioning
confidence: 99%